Divided, but not by much: The parties of the centre right between government and opposition - De Giorgi, Elisabetta (2021)
For the parties of the centre right, 2019 provided confirmation, at both the local and regional levels, that their alliance was solid. Although it is based entirely on strategic needs, it continues to bear fruit despite the fact that its internal distribution of power has completely changed. Matteo Salvini’s League has become the new dominant force within the coalition at national level and, in many cases, at regional level also. The extreme right Fratelli d’Italia is growing strongly. Forza Italia is declining ever more rapidly. In Parliament, changes have been decidedly more complex. At the beginning of the year, the three parties were divided between the government and the opposition. However, at the end of the year, the old allies found themselves once again united in opposition to the new government formed by the Democratic Party and the Five-star Movement. In this article, we re-examine the events that distinguished the year in question in order to understand to what extent and how the centre-right coalition changed over time. We also consider how the three parties reacted to the new political circumstances, which, until the end of the summer, meant that they were governing allies at the municipal and regional levels and on opposing sides at the national level.